Improved Dental Implant Drill Durability and Performance Using Heat and Wear Resistant Protective Coatings - Er, Nilay; ALKAN, ALPER; ALKAN, ALPER; Ilday, Serim; Bengu, Erman (My University, 2018)
The dental implant drilling procedure is an essential step for implant surgery, and frictional heat in bone during drilling is a key factor affecting the success of an implant. The aim of this study was to increase the dental implant drill lifetime and performance by using heat- and wear-resistant protective coatings to decrease the alveolar bone temperature caused by the dental implant drilling procedure. Commercially obtained stainless steel drills were coated with titanium aluminum nitride, diamond-like carbon, titanium boron nitride, and boron nitride coatings via magnetron-sputter deposition. Drilling was performed on bovine femoral cortical bone under the conditions mimicking clinical practice. Tests were performed under water-assisted cooling and under the conditions when no cooling was applied. Coated drill performances and durabilities were compared with those of three commonly used commercial drills with surfaces made from zirconia, black diamond. and stainless steel. Protective coatings with boron nitride, titanium boron nitride, and diamond-like carbon have significantly improved drill performance and durability. In particular, boron nitride-coated drills have performed within safe bone temperature limits for 50 drillings even when no cooling is applied. Titanium aluminium nitride coated drills did not show any improvement over commercially obtained stainless steel drills. Surface modification using heat-and wear-resistant coatings is an easy and highly effective way to improve implant drill performance and durability, which can improve the surgical procedure and the postsurgical healing period. The noteworthy success of different types of coatings is novel and likely to be applicable to various other medical systems.